2013
DOI: 10.1097/ajp.0b013e318247809a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Doses of Pregabalin on Morphine Analgesia in Advanced Cancer Patients

Abstract: Objectives: The aim of this study was to evaluate the opioid response in patients receiving morphine and pregabalin, independently from the presumed pain mechanisms, in comparison with patients receiving morphine treatment only.Methods: A multicenter prospective randomized controlled study was carried out in a sample of 70 advanced cancer patients with pain requiring strong opioids. Thirty-five patients (group MO) were randomized to receive sustained-release morphine using initial doses of 60 mg/day. Thirty-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Is there a researcher that can reproduce data suggesting that pregabalin works as a sole analgesic in cancer patients, even with a neuropathic component? For instance, pregabalin added to morphine did not provide any substantial analgesic benefit [13]. More meaningful reviews regarding antiepileptic drugs, do not support such hypothesis, even when they are given on top of opioid therapy [14].…”
mentioning
confidence: 99%
“…Is there a researcher that can reproduce data suggesting that pregabalin works as a sole analgesic in cancer patients, even with a neuropathic component? For instance, pregabalin added to morphine did not provide any substantial analgesic benefit [13]. More meaningful reviews regarding antiepileptic drugs, do not support such hypothesis, even when they are given on top of opioid therapy [14].…”
mentioning
confidence: 99%
“…Also, the mean percentage of change in pain was significantly greater in the pregabalin group: pregabalin: 46%, (95% CI: 40% to 53%); fentanyl: 22%, (95% CI: 15% to 30%), P < 0.001 . No significant differences were found in a study comparing morphine alone vs. a morphine–pregabalin combination in patients with advanced cancer, nor in a comparison with different doses of oxycodone–pregabalin combinations in non‐chemotherapy‐induced neuropathic pain …”
Section: Resultsmentioning
confidence: 87%
“…Only a few published studies address pregabalin use in cancer-related pain and do not specifically target CIBP [2529] and, with the exception of two trials [26, 28], these were open-label or observational studies. The results of one of the randomized controlled trials [26] suggested a morphine-sparing effect and improvement in neuropathic pain with pregabalin, whereas the other study suggested no analgesic benefit with the addition of pregabalin to morphine therapy [28]. Further well-conducted studies in this population would enable healthcare providers to make fully informed decisions regarding treatment.…”
Section: Discussionmentioning
confidence: 99%